13C NMR of DIPAC and DIPAB organic ferroelectrics. (24th September 2019) - Uskova, N I; Charnaya, E V; Podorozhkin, D Yu; Baryshnikov, S V; Milinskiy, A Yu; Egorova, I V
Abstract: The diisopropylammonium chloride (C6 H16 ClN, DIPAC) and diisopropylammonium bromide (C6 H16 BrN, DIPAB) molecular crystals are recently discovered ferroelectrics with sufficiently high spontaneous polarization and Curie temperature. We performed first studies of these crystals by 13 C NMR. CP MAS spectra were collected within large temperature ranges covering the Curie points. The reconstructive phase transition from the initial orthorhombic P 21 21 21 structure of DIPAB to the monoclinic ferroelectric P 21 structure leads to an abrupt alteration in the 13 C spectrum. The 13 C spectra for DIPAC and DIPAB in the ferroelectric P 21 phase are quite similar with four lines at lower frequencies, which correspond to the CH3 groups, and two lines with close chemical shifts, which correspond to two CH groups. The transition into the paraphase leads to gradual reduction of the interline distances in the low-frequency quadruplet and in the doublet. The step-like changes in the interline frequency shifts at this transition indicating its first order. The analysis of the spectrum evolution in the paraphase shows that only a CH group lays in the reflection plane above the P 21   →   P 21 /m transition, while the second CH group only moves closer to the reflection plane upon further heating.